(untitled) (Journal of Atomic and Molecular Sciences, 2015)
TExcited state reaction coordinates and the consequent energy profiles of a new Schiff base, N-salicilydenemethylfurylamine (SMFA), have been investigated with the MP2 and CASSCF method. The potential energy profiles of the ground and the lowest excited singlet state are calculated. The excited state potential energy profile shows a small barrier in the LIIC pathway of dissociation along the O-H stretching coordinate. This work suggests that there are two pathways in the photochemical reaction of SMFA. In one pathway, the photochemical product is the enol-type minimum. In the other pathway, the ESIPT reaction is observed and a excited state stationary structure is reached. The trans-keto and cis-keto type structures will be obtained from photoexcitation of the enol isomer. Two conical intersections between the ground and excited states act as the gates for nonadiabatic decay to the ground state.